Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

Online load balancing on uniform machines with limited migration - Maack, Marten (Operations Research Letters)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; Management Science and Operations Research; Software

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study - Hoffmann, Christina; Schneider, Tamara; Wannous, Chadia; Nyberger, Karolina; Haavardsson, Ingeborg; Gilmore, Brynne; Quigley, Paula; Winkler, Andrea S.; Ludwig, Sabine (Frontiers in Global Women's Health)
Background The COVID-19 pandemic has led to a deepening of existing inequalities and a rollback of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increase female leadership in global health. Here, the aim was to understand how the pandemic affects the private and professional lives of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspectives should be integrated into pandemic preparedness and how a women's network such as WGH helped them to overcome the impact of the pandemic were explored. Methods Qualitative semi-structured interviews were conducted in September 2020 with a sample size of nine highly educated women with a mean age of 42.1 years from the different WGH European chapters. The participants were informed of the study and were formally asked for their consent. The interviews were held in English via an online videoconference platform and lasted 20–25 min each. The interviews were audio recorded and transcribed verbatim. Thematic analysis was conducted according to Mayring Qualitative Content Analysis using MAXQDA. Results The pandemic has both positive and negative effects on the professional and private lives of women. It led to an increased workload and stress as well as pressure to publish on COVID-19-related themes. Increased childcare and household responsibilities represented a double burden. The available space was limited if other family members were also working from home. Positive aspects included more time for family or partners and reduced travel. The participants report on perceived gender differences in the experience of the pandemic. International cooperation is considered to be a key factor for future pandemic preparedness. Being part of a women's network such as WGH was perceived as being very supportive in difficult situations during the pandemic. Conclusion This study provides unique insights into the experiences of women working in global health in different European countries. The COVID-19 pandemic influences their professional and private lives. Perceived gender differences are reported and suggest the need for integrating gender perspectives in pandemic preparedness. Networks for women, such as WGH, can facilitate the exchange of information in crises and provide women with professional and personal support.
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Experimental and finite element method investigation on the compression behaviour of FCCZ and BCC lattice structures of additively manufactured Fe-3Si samples - Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The purpose of this study is to investigate the manufacturability of Fe-3Si lattice structures and the resulting mechanical properties. This study could lead to the successful processing of squirrel cage conductors (a lattice structure by design) of an induction motor by additive manufacturing in the future. Design/methodology/approach The compression behaviour of two lattice structures where struts are arranged in a face-centred cubic position and vertical edges (FCCZ), and struts are placed at body-centred cubic (BCC) positions, prepared by laser powder bed fusion (LPBF), is explored. The experimental investigations are supported by finite element method (FEM) simulations. Findings The FCCZ lattice structure presents a peak in the stress-strain curve, whereas the BCC lattice structure manifests a plateau. The vertical struts aligned along the compression direction lead to a significant increase in the load-carrying ability of FCCZ lattice structures compared to BCC lattice structures. This results in a peak in the stress-strain curve. However, the BCC lattice structure presents the bending of struts with diagonal struts carrying the major loads with struts near the faceplate receiving the least load. A high concentration of geometrically necessary dislocations (GNDs) near the grain boundaries along cell formation is observed in the microstructure. Originality/value To the best of the authors’ knowledge, this is the first study on additive manufacturing of Fe-3Si lattice structures. Currently, there are no investigations in the literature on the manufacturability and mechanical properties of Fe-3Si lattice structures.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (Procedia CIRP ICME)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy